METODE ACTIVITY BASED COSTING (ABC) DALAM PERHITUNGAN TARIF KAMAR RAWAT INAP - Perdana, Wildan Muhammad (Media Akuntansi dan Perpajakan Indonesia, 2020)
This study is conducted on the basis of the development of businessesthat lead to higher levels of business competition. Hospital is a nonprofitinstitution, and therefore the required accuracy of the management inmaking decisions, especially in determining inpatient room rates to maintainthe viability of the hospital. Activity based costing is considered toprovide more accurate than the traditional method for calculating the basicrate of hospitalization, so as to assist the management in setting room ratesof hospitalization that can be adapted to the resources used by each class. Inthis study, drivers used in the calculation of rates of hospitalization is, thenumber of days of hospitalization, the number of inpatients, electric powerconsumption (KWH), and room areas. The results showed that the calculationof the difference in activity based costing are high on the room typewith second class and third class.